Policy Evaluation Of Restructuring Street Vendors in Surakarta City (Study of Street Vendors in Monument Park Banjarsari and Street Vendors in Manahan Stadium) - Frahlevi Prajasari; Andy Fefta Wijaya; Choirul Saleh (Wacana Journal of Social and Humanity Studies, 2015)
This study examined the policy evaluation of restructuring street vendors in Surakarta city. Street vendors represent the economic actors in the informal sector of urban economic activity. The government of City/District usually removes these street vendors by disguising this activity behind the reason of structuring, . The study used descriptive research with a qualitative approach. The relocation of street vendors in Surakarta City is orderly and smooth without violence which may impact badly on physic and material because the government of Surakarta City, especially Surakarta Mayor, uses persuasive approach. Notoharjo Market is a relocation place for street vendors at Banjarsari Monument Park. In the beginning, Notoharjo Market is crowded with buyers but current days, street vendors who occupy Notoharjo Market complain about lack of buyers. The lack of buyers at Notoharjo Market is because the facilities previously provided by the government of Surakarta City are not well maintained. The government of Surakarta City must listening all complains of street vendors for the smoothness and orderliness of trading activity of street vendors. Not only listening, but the government of Surakarta City also gives appropriate and best solution to street vendors such that street vendors feel comfort in selling and their income is better than before.